Analysis of methods for determining the coordinates of rfid tags in the designated area - Babajanov, Elmurod; Jumaniyazova, Ulbosin (MMIT Proceedings, 2025)
This thesis highlights the application of RFID (Radio Frequency Identification) technologies in the field of localization, particularly in tracking objects and determining their coordinates within enclosed spaces. Through real-world examples, it demonstrates the use of RFID technology in healthcare, logistics, and security sectors, concluding that this approach is both economically and technically feasible